Workplace health in anesthesia team: A qualitative study in Iran - Khalafi, Ali; Sarvi Sarmeydani, Nooshin; Adarvishi, Sara (Frontiers in Public Health, 2023)
Background: All anesthesia providers, including nurse anesthetists and anesthesiologists work in a stressful environment with diverse tasks. The profession is characterized by high workload, both dependent and independent job descriptions, and unpredictable conditions. This study was designed and conducted to explain the factors affecting the workplace health of Iranian anesthesia teams. Methods: Twenty anesthesia team members including nurse anesthetists and anesthesiologists from 7 different hospitals were enrolled in this phenomenological research. The data were collected in 2022. Semi-structured interviews were used for data collection, and the transcripts were analyzed using qualitative content analysis. Findings: The most notable theme emerging from the data which was found to affect workplace health was consistency of anesthesia team. Other themes derived from the data included team tranquility and physical well-being. Conclusion: The participants' emphasis was more on behavioral and managerial factors affecting workplace health, and desirable interpersonal cooperation to create a suitable work environment for them was more prominent. These findings can raise the awareness of chief nurse anesthetists and planners to provide more effective teamwork, modify the job description structure, and reduce staff conflicts.